2014
DOI: 10.1007/s12012-014-9261-3
|View full text |Cite
|
Sign up to set email alerts
|

β1-Adrenoceptor Autoantibodies Affect Action Potential Duration and Delayed Rectifier Potassium Currents in Guinea Pigs

Abstract: β1-Adrenoceptor autoantibodies (β1-AAs) affect the action potential duration (APD) in cardiomyocytes and are related to ventricular arrhythmias. The delayed rectifier potassium current (I K) plays a crucial role in APD, but the effects of β1-AAs on I K have not been completely illuminated. This work aimed to observe the effects of β1-AAs on I K and APD and further explore the mechanisms of β1-AA-mediated ventricular arrhythmias. β1-AAs were obtained from sera of patients with coronary heart disease (CHD) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Our study confirmed that β 1 ‐AR mAbs prolonged MAPD 90−30 , which may be attributed to increased I Kr and I CaL and decreased I Ks of ventricular myocytes of guinea‐pigs (Zhao et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Our study confirmed that β 1 ‐AR mAbs prolonged MAPD 90−30 , which may be attributed to increased I Kr and I CaL and decreased I Ks of ventricular myocytes of guinea‐pigs (Zhao et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…) and I Kr (Zhao et al . ), but decrease I Ks by binding with β 1 ‐AR (Medei et al . ) in the ventricular myocardium.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations